Reforming Malaysia’s juvenile justice system: a critical analysis of pre-trial diversion within the framework of international standards - Nor Aida Ab. Kadir; Aminuddin Mustaffa; Sholahuddin Al-Fatih; Nik Nur Nasyuha Nik Ahmad Rizal; Vita Mahardhika (Faculty of Law, University of Muhammadiyah Malang, 2025)
This paper aims to scrutinise the Malaysian juvenile justice system and the negative consequences of the lack of pre-trial alternative measures in dealing with children. Juvenile delinquency is a social problem that has attracted numerous discussions from different quarters. One of the primary issues in this area is how to respond to complex, multifaceted problems involving children in conflict with the law. Through doctrinal analysis and comparative frameworks with international standards and legal practice in England and New Zealand, this study highlights the positive impact of diversionary approaches on recidivism, rehabilitation, and restorative justice. Malaysia’s heavy reliance on formal adjudication is inconsistent with several international standards. This paper advocates amending the Child Act 2001 and the Criminal Procedure Code to implement pre-trial diversion, with police and prosecutorial discretion to encourage restorative justice alternatives in minor and non-violent cases. This change would align Malaysia’s system with international norms, improve children's rights, and advance the justice system toward greater rehabilitation and restoration.